Nrf2 regulates downstream genes by targeting miR-29b in severe asthma and the role of grape seed proanthocyanidin extract in a murine model of steroid-insensitive asthma - Yan Qian; Yun Sun; Yi Chen; Zhengdao Mao; Yujia Shi; Di Wu; Bin Gu; Zhiguang Liu; Qian Zhang (Taylor & Francis Group, 2022)
Context Grape seed proanthocyanidin extract (GSPE) is effective in treating severe asthma (SA). Objective To examine the relationship between Nrf2-miR-29b axis and SA, and to detect whether preventive use of GSPE relieves SA via it. Materials and methods We recruited 10 healthy controls, 10 patients with non-severe asthma (nSA), and 9 patients with SA from February 2017 to December 2017. Peripheral blood mononuclear cells from these volunteers were extracted. A murine model of steroid-insensitive asthma was established in six-week-old female BALB/c mice that were sensitised and challenged with OVA, Al(OH)3 and LPS for 31 days. Mice in the treated groups were injected with DXM (5 mg/kg/d), with or without GSPE (100 mg/kg/d). Control group received PBS. We performed quantitative real-time PCR, western blot and luciferase reporter assay in animal and cell models. Results SA group demonstrated significantly lower concentrations of Nrf2 protein, Nrf2 mRNA, and miR-29b than nSA group and control group. Conversely, higher levels of platelet derived growth factor C (PDGFC), phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1), and collagen type III alpha 1 (COL3A1) were measured in SA than in the other two groups. PDGFC, PIK3R1, and COL3A1 were the target genes of miR-29b. GSPE + DXM significantly elevated the expression of Nrf2 (+188%), Nrf2 mRNA (+506%), and miR-29b (+201%), and significantly reduced the expression of PDGFC (−72%), PIK3R1 (−40%), and COL3A1 (−65%) compared with OVA + LPS. Conclusions Nrf2-miR-29b axis is involved in the pathogenesis of SA. GSPE, as an adjuvant drug, maybe a potential therapeutic agent for SA.